Algorithms and data structures : 10th International Workshop, WADS 2007, Halifax, Canada, August 15-17, 2007 : proceedings - Workshop on Algorithms and Data Structures; Dehne, Frank; Sack, Jörg-Rüdiger; Zeh, Norbert (Lecture Notes in Computer Science, 2007)
The papers in this volume were presented at the 10th Workshop on Algorithms and Data Structures (WADS 2005). The workshop took place August 15 - 17, 2007, at Dalhousie University, Halifax, Canada. The workshop alternates with the Scandinavian Workshop on Algorithm Theory (SWAT), continuing the t- dition of SWAT and WADS starting with SWAT 1988 and WADS 1989. From 142 submissions, the Program Committee selected 54 papers for presentation at the workshop. In addition, invited lectures were given by the following dist- guished researchers: Je? Erickson (University of Illinois at Urbana-Champaign) and Mike Langston (University of Tennessee). On behalf of the Program Committee, we would like to express our sincere appreciation to the many persons whose e?ort contributed to making WADS 2007 a success. These include the invited speakers, members of the Steering and ProgramCommittees, the authorswho submitted papers, andthe manyreferees who assisted the Program Committee. We are indebted to Gerardo Reynaga for installing and modifying the submission software, maintaining the submission server and interacting with authors as well as for helping with the preparation of the program.